PERAN PANITIA PEMILIHAN UMUM AKSES PENYANDANG CACAT (PPUA PENCA) DALAM SOSIALISASI POLITIK BAGI MASYARAKAT DIFABEL DALAM PEMILIHAN UMUM GUBERNUR DKI JAKARTA 2013 - Oktaviawan Yandarisman; Fitriyah .; Nunik Retno H (Journal of Politic and Government Studies, 2014)
Election is one form of political participation . Every citizen has the right toparticipate in the General Election without exception . So also with people with disabilities .Communities with special needs is also entitled to participate in the election .. This studyaims to examine the role of political socialization PPUA Disabled in the Jakarta gubernatorialelection in 2013 for the people with disabilities . Disabled PPUA as NGOs do play a role inpolitical socialization of people with disabilities in the elections , in order to obtain equalrights and obligations in politics , so there is no gap between people with disabilities with thecommunity at large . Governor Election is one means of political participation for peoplewith disabilities who participate in it PPUA Disabled . Socialization process is carried out tothe people with disabilities to socialize through seminars conducted in five areas of Jakartaand through methods of mentoring as a form of responsibility on Disabled PPUA as agenciesthat serve and assist the electoral process for people with disabilitiesKeywords: PPUA Disabled, Role, People with disabilities, Socialization